Breast and ovarian cancer risks in a large series of clinically ascertained families with a high proportion of BRCA1 and BRCA2 Dutch founder mutations. Issue 2 (27th November 2013) - Brohet, Richard M; Velthuizen, Maria E; Hogervorst, Frans B L; EJ Meijers-Heijboer, Hanne; Seynaeve, Caroline; Collée, Margriet J; Verhoef, Senno; Ausems, Margreet G E M; Hoogerbrugge, Nicoline; van Asperen, Christi J; Gómez García, Encarna; Menko, Fred; et al.
Abstract : Background: BRCA1 or BRCA2 mutations confer increased risks of breast and ovarian cancer, but risks have been found to vary across studies and populations. Methods: We ascertained pedigree data of 582 BRCA1 and 176 BRCA2 families and studied the variation in breast and ovarian cancer risks using a modified segregation analysis model. Results: The average cumulative breast cancer risk by age 70 years was estimated to be 45% (95% CI 36 to 52%) for BRCA1 and 27% (95% CI 14 to 38%) for BRCA2 mutation carriers. The corresponding cumulative risks for ovarian cancer were 31% (95% CI 17 to 43%) for BRCA1 and 6% (95% CI 2 to 11%) for BRCA2 mutation carriers. In BRCA1 families, breast cancer relative risk (RR) increased with more recent birth cohort (pheterogeneity = 0.0006) and stronger family histories of breast cancer (pheterogeneity <0.001). For BRCA1, our data suggest a significant association between the location of the mutation and the ratio of breast to ovarian cancer (p<0.001). By contrast, in BRCA2 families, no evidence was found for risk heterogeneity by birth cohort, family history or mutation location. Conclusions: BRCA1 mutation carriers conferred lower overall breast and ovarian cancer risks than reported so far, while the estimates of BRCA2 mutations were among the lowest. The low estimates for BRCA1 might be due to older birth cohorts, a moderate family history, or founder mutations located within specific regions of the gene. These results are important for a more accurate counselling of BRCA1/2 mutation carriers.